The Correlation Between Vocabulary Mastery and Students’ Preferences on Short Stories - Putri, May Lucyana Kartono; Megawati, Fika (Indonesian Journal Publisher, 2024)
The purpose of this study was to determine whether there is a correlation between vocabulary mastery and short story liking at SMP Muhammadiyah 5 Tulangan. The method used in this research is correlation method. The data source of this research was 7th grade students of SMP Muhammadiyah 5 Tulangan with a total of 30 participants. The data collection technique used questionnaires and tests. The sample used was 7th grade students with a total of 30 students. The data analysis used is Product Moment correlation test. The results showed that there was no significant relationship between vocabulary mastery and liking short stories of 7th grade students of SMP Muhammadiyah 5 Tulangan. This is proven by the correlation coefficient of 0.08 and 0.00 greater than 0.05 at a significant level of 5%. This proves that at a significant level of a = 0.05 or at a confidence level of 95% there is no significant relationship between vocabulary mastery and liking short stories in Muhammadiyah 5 Tulangan Junior High School students.